Web-Based Information System for Matching Soil Fertility and pH with Plant Types - Dinata, Firda Arya; Sujono, Sujono; Sufaidah, Siti (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
A web-based information system to match soil fertility and pH with crop types is an innovative agricultural sector solution aiming to increase crop yields. This study focuses on the importance of matching soil conditions for the kinds of crops planted, where soil pH and nutrients are key factors. Many farmers cannot access adequate information about their soil conditions, so planting is often suboptimal. Through this system, farmers can easily access recommendations for crop types that are suitable for their soil conditions, generated from analysis of soil pH and fertility data.